Le personnage d’Arachné dans le roman Die letzte Welt de Christoph Ransmayr - Cailleux, Dorothée (Amaltea. Revista de Mitocrítica, 2010)
In his novel Die letzte Welt, published in 1988, the Austrian writer Christoph Ransmayr revives the ovidian myths by setting his plot in a mysterious town inhabited by characters coming from the Metamorphoses, among which the old deaf-mute spinner Arachne. This article aims at studying the function of this character in the novel, sheding light on the way Ransmayr uses the original myth to give him a new meaning. It seems indeed that this character plays a particular role and becomes the symbol of the invincibility of art, despite the weakness of the artist.
Keywords: Ransmayr; Die letzte Welt; Metamorphosis; Arachne; Myth; Ovid; Intertextuality; Art